Faktor-Faktor yang Mempengaruhi Struktur Modal Perusahaan Pertambangan Sub Sektor Batubara yang Terdaftar di Bursa Efek Indonesia - Bako, Seven Marganda (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to empirically analyze the factors that influence capital structure include profitability proxied by return on assets/ROA, asset structure, liquidity as proxied by current ratio/CR, and company size in coal mining subsector companies listed on the Indonesia Stock Exchange for the period 2014 to 2018. The research sample was taken using the purposive sampling method, so that 10 companies were selected that met the specified criteria. The data analysis applied was panel data regression, with the selected model being the Random Effect Model. From the regression results, the Adjusted R-square (R²) value reached 0.434760, which means that the independent variables were able to explain 43.47% of the variation in the dependent variable, while the rest, which was 56.53%, was explained by other factors outside the study. The F test also showed a value of 0.00000, smaller than the significance level of α = 0.05, so it can be concluded that simultaneously the independent variables have a significant effect on capital structure. Meanwhile from the results of partial testing, the liquidity variable was proven to have a significant negative influence on capital structure, while profitability, asset structure, and company size do not have a significant impact.